2015
DOI: 10.2174/1874285801509010167
|View full text |Cite
|
Sign up to set email alerts
|

The Murine Lung Microbiome Changes During Lung Inflammation and Intranasal Vancomycin Treatment

Abstract: Most microbiome research related to airway diseases has focused on the gut microbiome. This is despite advances in culture independent microbial identification techniques revealing that even healthy lungs possess a unique dynamic microbiome. This conceptual change raises the question; if lung diseases could be causally linked to local dysbiosis of the local lung microbiota. Here, we manipulate the murine lung and gut microbiome, in order to show that the lung microbiota can be changed experimentally. We have u… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
43
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 58 publications
(44 citation statements)
references
References 57 publications
1
43
0
Order By: Relevance
“…Currently, there is no evidence for a direct influence of intestinal dysbiosis caused by oral antibiotics on skin microbiota. However, it must be stressed that each barrier site exposed to the external world harbors its own distinct microbiota, which can be modulated by local inflammation as has been demonstrated for lungs (Barfod et al, 2015), and is likely the case for skin as well. A prior study found an enrichment in Rhodotorula in the skin of patients with early SSc compared with controls (Arron et al, 2014).…”
Section: Discussionmentioning
confidence: 99%
“…Currently, there is no evidence for a direct influence of intestinal dysbiosis caused by oral antibiotics on skin microbiota. However, it must be stressed that each barrier site exposed to the external world harbors its own distinct microbiota, which can be modulated by local inflammation as has been demonstrated for lungs (Barfod et al, 2015), and is likely the case for skin as well. A prior study found an enrichment in Rhodotorula in the skin of patients with early SSc compared with controls (Arron et al, 2014).…”
Section: Discussionmentioning
confidence: 99%
“…We cannot rule out the possibility that changes in either the lung or oral microbiome also impacted responses to O 3 . We examined the gut microbiome because we have previously reported that it is the gut rather than the lung microbiome that accounts for effects of antibiotics and germ free conditions on responses to O 3 [33]: in lean male mice, oral vancomycin reduces O 3 -induced AHR [33] but does not affect the lung microbiome [45], even though it does affect the gut microbiome [33].…”
Section: Discussionmentioning
confidence: 99%
“…Although the existence of a gut-lung axis has been clearly established (Figure 1), the contribution of the airway resident microbiota to this axis remains to be elucidated. Even if it presently appears difficult to specifically target the lung microbiota without distal effect on other communities, its role needs be carefully evaluated, possibly by using intranasally delivered antibiotics in order to modify the lung communities (Barfod et al, 2015). Another possible approach involves the introduction, via the oropharyngeal route, of probiotics, which seem to modulate lung immunity, increase protection against respiratory pathogens, and reduce lung damage.…”
Section: Perspectivementioning
confidence: 99%